HIV Suppression among Patients on Treatment in Vietnam: A Review of HIV Viral Load Testing in a Public Urban Clinic in Ho Chi Minh City - T. Tony Trinh; Brian T. Montague; Timothy P. Flanigan; Hoang My Gerard (AIDS Research and Treatment)
Background. There are few reports of HIV viral load (VL) testing among patients on ART in Vietnam. Methods. From a public clinic in Ho Chi Minh City (HCMC), we reviewed cases of VL measurements from adults on ART. Results. We identified 228 cases. Median age was 30 years (27–34), 85% were male, and 77% had a history of IDU. The mean ART duration was 26 months (95% CI 25–27); d4T/3TC/NVP was the most common regimen. Viral suppression was seen in 160/228 (70%). Viremia (>1000 copies/mL) was associated with prior ART exposure (OR 5.68, ) and immunologic failure (OR 4.69, ). Targeted testing accounted for 13% of cases, only half of which yielded viremia. Conclusion. We demonstrate a high HIV suppression rate among patients on ART in HCMC, Vietnam. In this setting, routine testing detects viremia missed by targeted testing.